Chimera holding heraldic shield - Ghosh, Ayan (Jio Institute, 2023)
Though they are mistaken as lions, the 'lions' at the BMC building are chimeras—a mix of various animals—hence they appear with wings and a serpentine tail. The chimera has been attributed to the British dominance over land, sea and air. However, it is more likely that the motif was inspired from the flag of the Republic of Venice, which featured winged lions, one of the many elements Frederick W. Stevens incorporated from Venetian Gothic architecture.